A Dual Role of Sox2 on Atoh1 Regulation. (2nd September 2014) - Cheng, Yenfu; Petrillo, Marco; Edge, Albert S.
Abstract : Objectives: Loss of mammalian auditory hair cells is usually permanent, and there is currently no method to recover hearing after hair cell damage. Atoh1, a basic helix‐loop‐helix transcription factor, plays a critical role in formation of hair cells. Experiments overexpressing Atoh1 in the inner ear via gene transfer have shown new hair cell formation and improved hearing in tested animals. However, we do not currently know how cells regulate Atoh1. We found that Sox2, a pluripotency marker for stem cells and also present in inner ear stem cells, is involved in the regulation of Atoh1. In this study, we try to understand the role of Sox2 in the regulation of Atoh1 for hair cell formation. Methods: A 293T cell line that stably expresses Atoh1 was developed for Atoh1 expression assays. Atoh1 level was measured by real time qPCR and western blot. Mass spectrometry was used to identify Atoh1 protein partners. Plasmids transfection was used for gain‐of‐function studies, while small interfering RNA was used for loss‐of‐function studies. Results: We found that Sox2 upregulates Atoh1 at the transcriptional level but also enhances Atoh1 degradation post‐translationally. We found that Sox2 is involved in the major post‐translational regulation, the ubiquitin‐proteasomal pathway, which is the control mechanism through which Sox2 regulates specification of hair cells. Conclusions: Sox2 has dual role on Atoh1 regulation: upregulation of Atoh1 transcription by binding to Atoh1 3′enhancer, and post‐translational Atoh1 degradation through activating ubiquitin‐proteasome pathway.